2008
DOI: 10.1073/pnas.0809807105
|View full text |Cite
|
Sign up to set email alerts
|

Human multipotent stromal cells from bone marrow and microRNA: Regulation of differentiation and leukemia inhibitory factor expression

Abstract: We observed that microRNAs (miRNAs) that regulate differentiation in a variety of simpler systems also regulate differentiation of human multipotent stromal cells (hMSCs) from bone marrow. Differentiation of hMSCs into osteoblasts and adipocytes was inhibited by using lentiviruses expressing shRNAs to decrease expression of Dicer and Drosha, two enzymes that process early transcripts to miRNA. Expression analysis of miRNAs during hMSC differentiation identified 19 miRNAs that were up-regulated during osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
156
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 36 publications
4
156
0
3
Order By: Relevance
“…37,38 hsa-miR-346 may function in the differentiation of mesenchymal stem cells from bone marrow by targeting the leukaemia inhibitory factor. 39 Our data indicate that these miRNAs are also associated with prostate cancer and could be useful circulating markers of this disease. Using a large prostate cancer expression dataset from the MSKCC cohort, we showed that the levels of hsa-miR-141, hsa-miR-298 and hsa-miR-375 were increased in localized primary tumors and metastases.…”
Section: Discussionmentioning
confidence: 66%
“…37,38 hsa-miR-346 may function in the differentiation of mesenchymal stem cells from bone marrow by targeting the leukaemia inhibitory factor. 39 Our data indicate that these miRNAs are also associated with prostate cancer and could be useful circulating markers of this disease. Using a large prostate cancer expression dataset from the MSKCC cohort, we showed that the levels of hsa-miR-141, hsa-miR-298 and hsa-miR-375 were increased in localized primary tumors and metastases.…”
Section: Discussionmentioning
confidence: 66%
“…It has previously been shown that miRNA expression and processing are required for other differentiation processes of the mesenchymal lineage, including osteocyte, adipocyte, 24 skeletal muscle (miR181a), 26 and cardiac muscle (miR-1 and miR-133). 27 This is the first report, however, of miRNA requirement for smooth muscle differentiation of mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several let-7 members, including 7b, are also modulated during osteocytic and adipocytic differentiation. 24 Other miRNAs in the SM differentiation signature include miR-155, with a known role in B-cell differentiation, 29 and miR-18a, a member of the miR-17-92 family, which regulates stem cell renewal and displays pro-proliferative and oncogenic potential. 13 Our experiments show that at least some of these miRNAs (ie, miR-155) play an active role in SM differentiation and are not mere byproducts of the actual 'driver' alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Very few studies have evaluated DICER1 or DROSHA activity in MSC and they focused on their role in differentiation of MSCs. 20,21 Thus, to gain insight into the biological effects of low DICER1 and DROSHA expression in MSC-MDS, we further analyzed mature microRNA expression profile, showing a trend towards global downexpression in MDS-MSC when compared with normal MSC. These results could be associated with the inherent biological diversity among MDS subtypes.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%